Step * 1 1 3 of Lemma separable-kernel-properties


1. rv InnerProductSpace
2. Point(rv)
3. {h:Point(rv)| h ⋅ r0}  ⟶ ℝ ⟶ ℝ
4. ∀h1,h2:{h:Point(rv)| h ⋅ r0} . ∀t1,t2:ℝ.  (f h1 t1 ≠ h2 t2  (h1 h2 ∨ t1 ≠ t2))
5. ∀h:{h:Point(rv)| h ⋅ r0} ((f r0) r0)
6. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t1,t2:ℝ.  ((t1 < t2)  ((f t1) < (f t2)))
7. ∀h:{h:Point(rv)| h ⋅ r0} . ∀r:ℝ.  ∃t:ℝ((f t) r)
8. : ℝ ⟶ ℝ
9. {h:Point(rv)| h ⋅ r0}  ⟶ ℝ
10. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t:ℝ.  ((f t) ((g t) (k h)))
11. ∀h:{h:Point(rv)| h ⋅ r0} h ≠ r0
12. 0 ≠ r0
13. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t:ℝ.  ((f t) (((g t) (k 0)) ((λh.(k h/k 0)) h)))
14. ((g r0) (k 0)) r0
15. ((λh.(k h/k 0)) 0) r1
16. ∀t,s:ℝ.  ((t < s)  (((g t) (k 0)) < ((g s) (k 0))))
17. ∀t:ℝ. ∃s:ℝ(((g s) (k 0)) t)
18. ∀h1,h2:{h:Point(rv)| h ⋅ r0} .  ((λh.(k h/k 0)) h1 ≠ h.(k h/k 0)) h2  h1 h2)
19. : ℝ
20. : ℝ
21. (g t) (k 0) ≠ (g s) (k 0)
⊢ t ≠ s
BY
((FLemma `rneq-rmul` [-1] THENA Auto) THEN -1) }

1
1. rv InnerProductSpace
2. Point(rv)
3. {h:Point(rv)| h ⋅ r0}  ⟶ ℝ ⟶ ℝ
4. ∀h1,h2:{h:Point(rv)| h ⋅ r0} . ∀t1,t2:ℝ.  (f h1 t1 ≠ h2 t2  (h1 h2 ∨ t1 ≠ t2))
5. ∀h:{h:Point(rv)| h ⋅ r0} ((f r0) r0)
6. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t1,t2:ℝ.  ((t1 < t2)  ((f t1) < (f t2)))
7. ∀h:{h:Point(rv)| h ⋅ r0} . ∀r:ℝ.  ∃t:ℝ((f t) r)
8. : ℝ ⟶ ℝ
9. {h:Point(rv)| h ⋅ r0}  ⟶ ℝ
10. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t:ℝ.  ((f t) ((g t) (k h)))
11. ∀h:{h:Point(rv)| h ⋅ r0} h ≠ r0
12. 0 ≠ r0
13. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t:ℝ.  ((f t) (((g t) (k 0)) ((λh.(k h/k 0)) h)))
14. ((g r0) (k 0)) r0
15. ((λh.(k h/k 0)) 0) r1
16. ∀t,s:ℝ.  ((t < s)  (((g t) (k 0)) < ((g s) (k 0))))
17. ∀t:ℝ. ∃s:ℝ(((g s) (k 0)) t)
18. ∀h1,h2:{h:Point(rv)| h ⋅ r0} .  ((λh.(k h/k 0)) h1 ≠ h.(k h/k 0)) h2  h1 h2)
19. : ℝ
20. : ℝ
21. (g t) (k 0) ≠ (g s) (k 0)
22. t ≠ s
⊢ t ≠ s

2
1. rv InnerProductSpace
2. Point(rv)
3. {h:Point(rv)| h ⋅ r0}  ⟶ ℝ ⟶ ℝ
4. ∀h1,h2:{h:Point(rv)| h ⋅ r0} . ∀t1,t2:ℝ.  (f h1 t1 ≠ h2 t2  (h1 h2 ∨ t1 ≠ t2))
5. ∀h:{h:Point(rv)| h ⋅ r0} ((f r0) r0)
6. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t1,t2:ℝ.  ((t1 < t2)  ((f t1) < (f t2)))
7. ∀h:{h:Point(rv)| h ⋅ r0} . ∀r:ℝ.  ∃t:ℝ((f t) r)
8. : ℝ ⟶ ℝ
9. {h:Point(rv)| h ⋅ r0}  ⟶ ℝ
10. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t:ℝ.  ((f t) ((g t) (k h)))
11. ∀h:{h:Point(rv)| h ⋅ r0} h ≠ r0
12. 0 ≠ r0
13. ∀h:{h:Point(rv)| h ⋅ r0} . ∀t:ℝ.  ((f t) (((g t) (k 0)) ((λh.(k h/k 0)) h)))
14. ((g r0) (k 0)) r0
15. ((λh.(k h/k 0)) 0) r1
16. ∀t,s:ℝ.  ((t < s)  (((g t) (k 0)) < ((g s) (k 0))))
17. ∀t:ℝ. ∃s:ℝ(((g s) (k 0)) t)
18. ∀h1,h2:{h:Point(rv)| h ⋅ r0} .  ((λh.(k h/k 0)) h1 ≠ h.(k h/k 0)) h2  h1 h2)
19. : ℝ
20. : ℝ
21. (g t) (k 0) ≠ (g s) (k 0)
22. 0 ≠ 0
⊢ t ≠ s


Latex:


Latex:

1.  rv  :  InnerProductSpace
2.  e  :  Point(rv)
3.  f  :  \{h:Point(rv)|  h  \mcdot{}  e  =  r0\}    {}\mrightarrow{}  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
4.  \mforall{}h1,h2:\{h:Point(rv)|  h  \mcdot{}  e  =  r0\}  .  \mforall{}t1,t2:\mBbbR{}.    (f  h1  t1  \mneq{}  f  h2  t2  {}\mRightarrow{}  (h1  \#  h2  \mvee{}  t1  \mneq{}  t2))
5.  \mforall{}h:\{h:Point(rv)|  h  \mcdot{}  e  =  r0\}  .  ((f  h  r0)  =  r0)
6.  \mforall{}h:\{h:Point(rv)|  h  \mcdot{}  e  =  r0\}  .  \mforall{}t1,t2:\mBbbR{}.    ((t1  <  t2)  {}\mRightarrow{}  ((f  h  t1)  <  (f  h  t2)))
7.  \mforall{}h:\{h:Point(rv)|  h  \mcdot{}  e  =  r0\}  .  \mforall{}r:\mBbbR{}.    \mexists{}t:\mBbbR{}.  ((f  h  t)  =  r)
8.  g  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
9.  k  :  \{h:Point(rv)|  h  \mcdot{}  e  =  r0\}    {}\mrightarrow{}  \mBbbR{}
10.  \mforall{}h:\{h:Point(rv)|  h  \mcdot{}  e  =  r0\}  .  \mforall{}t:\mBbbR{}.    ((f  h  t)  =  ((g  t)  *  (k  h)))
11.  \mforall{}h:\{h:Point(rv)|  h  \mcdot{}  e  =  r0\}  .  k  h  \mneq{}  r0
12.  k  0  \mneq{}  r0
13.  \mforall{}h:\{h:Point(rv)|  h  \mcdot{}  e  =  r0\}  .  \mforall{}t:\mBbbR{}.    ((f  h  t)  =  (((g  t)  *  (k  0))  *  ((\mlambda{}h.(k  h/k  0))  h)))
14.  ((g  r0)  *  (k  0))  =  r0
15.  ((\mlambda{}h.(k  h/k  0))  0)  =  r1
16.  \mforall{}t,s:\mBbbR{}.    ((t  <  s)  {}\mRightarrow{}  (((g  t)  *  (k  0))  <  ((g  s)  *  (k  0))))
17.  \mforall{}t:\mBbbR{}.  \mexists{}s:\mBbbR{}.  (((g  s)  *  (k  0))  =  t)
18.  \mforall{}h1,h2:\{h:Point(rv)|  h  \mcdot{}  e  =  r0\}  .    ((\mlambda{}h.(k  h/k  0))  h1  \mneq{}  (\mlambda{}h.(k  h/k  0))  h2  {}\mRightarrow{}  h1  \#  h2)
19.  t  :  \mBbbR{}
20.  s  :  \mBbbR{}
21.  (g  t)  *  (k  0)  \mneq{}  (g  s)  *  (k  0)
\mvdash{}  t  \mneq{}  s


By


Latex:
((FLemma  `rneq-rmul`  [-1]  THENA  Auto)  THEN  D  -1)




Home Index